Differentiated Learning Strategies: Tailoring Islamic Education to Meet Diverse Student Needs - Furqon, Zenal; Haryanti, Erni (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
The purpose of this research is to find out how the differentiation strategy in PAI subjects is able to facilitate the level of diversity of students, differentiated learning is an approach by adjusting the process, content, or learning products based on the needs, interests, or level of learning readiness of students with this it will be able to help to increase the success rate of graduates or learning outcomes of a person, because the differentiation process will make students learn according to their will and will which will lead to their interests and talents. The method used in this research is the literature review method, this is because it allows researchers to explore key concepts based on relevant research and sources. The results of this study show that the differentiation strategy can be applied in PAI learning especially in facilitating the diversity of students who are different from one another, differentiation can be done from various aspects such as content, process, product and even in terms of learning environment so that it can increase students' interest in learning which in turn will have an impact on the level of understanding of students, therefore this differentiation strategy can be applied in PAI learning.